Collaborative Online Learning Based on The Inter-University Learning Management System - Soetopo, Dhalia; Nurullita, Hervina; Mursidi, Agus; Shomad, Abdul; Tejawati, Ni Luh Putu; Pramartha, I Nyoman Bayu (Jurnal Paedagogy, 2023)
This research aims to describe the implementation of online learning between PGRI Banyuwangi University and PGRI Mahadewa University Indonesia during the Covid-19 pandemic. So that the learning process continues to run well and keeps the quality of education high, universities collaborate in organizing a flexible learning system. The method used in this research was descriptive qualitative. Data was collected using literature study, document analysis, observation, and interviews. The informants in this research were 30 students from both universities who took Cultural History courses. The research results showed that this collaborative learning focused on online learning design to create social interaction and a humanist side of learning. It leads to effective learning, namely social interaction in the online learning process and performance between students. Collaboration-based online learning design was managed in the following way: (1) collaboration-based online learning planning begins with needs analysis; (2) the implementation of collaboration-based online learning is carried out by providing teaching materials in the LMS and then accessing them independently. Furthermore, the effectiveness of collaboration-based online learning was obtained through involvement in completing assignments through integrated online worksheets and group work.